Meteorologisches und Ozeanographisches aus der "Grönlandfahrt" - Wegner, Gerd (DEU, 2020)
In the seventeenth and eighteenth century, on journeys within the framework of the "Greenland expeditions" - whaling in the northernmost area of the North Atlantic - a wide range of written records were kept. Apart from the actual whaling events themselves, they described meteorological and oceanographic observations. In combination with natural history compendia, this data provides good insights and an initial basis for understanding complex interrelationships in an educational manner. Within the framework of this article, meteorological and oceanographic observations from four works originating in the context of Hamburg whaling activities around 1700 will be discussed.